2017
DOI: 10.1016/j.neuropsychologia.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI investigation of the relationship between future imagination and cognitive flexibility

Abstract: While future imagination is largely considered to be a cognitive process grounded in default mode network activity, studies have shown that future imagination recruits regions in both default mode and frontoparietal control networks. In addition, it has recently been shown that the ability to imagine the future is associated with cognitive flexibility, and that tasks requiring cognitive flexibility result in increased coupling of the default mode network with frontoparietal control and salience networks. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 120 publications
1
27
0
1
Order By: Relevance
“…Interestingly, in other studies we have found that when the components comprising novel future events are disparate, construction times and perceived difficulty are higher still-and incorporated detail lower-compared to novel future events including related components (Roberts, Wiebels, et al, 2017;van Mulukom et al, 2016). Our exploratory analyses in Study 1, showing that constructive demands are modulated by plausibility, such that less plausible events are less detailed but take longer to imagine, provide further evidence for this idea.…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, in other studies we have found that when the components comprising novel future events are disparate, construction times and perceived difficulty are higher still-and incorporated detail lower-compared to novel future events including related components (Roberts, Wiebels, et al, 2017;van Mulukom et al, 2016). Our exploratory analyses in Study 1, showing that constructive demands are modulated by plausibility, such that less plausible events are less detailed but take longer to imagine, provide further evidence for this idea.…”
Section: Discussionsupporting
confidence: 60%
“…Finally, cognitive evidence points toward a role for episodic future thinking in shaping an individual’s sense of self and identity (9293), both cognitive and neuroimaging evidence indicate a connection between episodic future thinking and divergent creative thinking (9495), and studies of spatial navigation show that episodic simulation makes an important functional contribution to planning routes and achieving navigational goals (see Box 3). …”
Section: Functions Of Episodic Future Thinkingmentioning
confidence: 99%
“…Interestingly, the brain regions that most contributed to these increased functional connectivity patterns included those areas that belong to the default mode network (DMN) (e.g., the medial prefrontal cortex, posterior cingulate, and temporo-parietal junction). Although the precise role of each region within the DMN is still matter of debate (Leech, Kamourieh, Beckmann, & Sharp, 2011 ), there is robust evidence that the DMN as a whole is involved in several aspects of human cognition and behaviour, including episodic and semantic memory, imagination, decision-making, and theory of mind (Roberts et al, 2017 ; Schacter, 2012 ; Schacter et al, 2012 ; Schacter, Benoit, De Brigard, & Szpunar, 2015 ). It is thus reasonable to expect that enhanced functional connectivity patterns within and across the DMN is linked with FFM personality traits that predict “positive” and favourable behavioural outcomes, although caution is always warranted when making reverse inferences in interpreting neuroimaging findings (Poldrack, 2006 ).…”
mentioning
confidence: 99%